The Role of Immersive Murder Mystery Games in Preventing Telecom Fraud among College Students - Sirui Xu (International Journal of Social Sciences and Public Administration, 2026)
Telecom fraud represents a typical security risk on university campuses, severely undermining campus stability and safety. As fraudulent tactics continue to evolve, traditional anti-fraud models struggle to keep pace with the increasingly severe landscape. Exploring efficient anti-fraud education methods tailored to college students has thus become a priority for higher education institutions, with immersive murder mystery games offering a novel approach to innovating campus anti-fraud initiatives. Grounded in the practical dilemmas of current anti-fraud education and supported by situated learning and experiential education theories, this paper systematically analyzes the core advantages and mechanisms of applying immersive murder mystery games to anti-fraud education for college students. It elucidates their multi-dimensional educational logic and proposes diverse practical pathways for implementation in universities. The study demonstrates that immersive murder mystery games can effectively address the shortcomings of traditional anti-fraud education, enhance its quality and efficacy, and hold significant theoretical and practical value for innovating campus safety education models and strengthening anti-fraud defenses.